The segment polarity gene armadillo encodes a functionally modular protein that is the Drosophila homolog of human plakoglobin. - Peifer, M.; Wieschaus, E. (Cell, 1990)
The Drosophila segment polarity gene armadillo is required for pattern formation within embryonic segments and imaginal discs. We have found that armadillo is highly conserved during evolution; it is 63% identical to human plakoglobin, a protein found in adhesive junctions joining epithelial and other cells. We have examined arm protein localization in a number of larval tissues and found that arm protein accumulation within cells shares many features with the accumulation of plakoglobin. We have compared the phenotype and molecular lesions responsible for the different arm mutations. Surprisingly, severely truncated proteins retain some function; the degree of function is strictly correlated with the length of the truncated protein, suggesting that the internally repetitive arm protein is modular in function. We present a possible model for the cellular role of arm.